Development of iBeacon application 2 - Siek, Ming Jun (Nanyang Technological University, 2021)
Navigation plays an important role in our current society. We are always navigating from one place to another. In the past, we used physical map for navigation but with the advancement of technology, we have GPS and Google Map which allows for navigation at the tip of our fingers. However, it is still not possible to use these technologies to solve indoor localization and indoor navigation. With the help of Bluetooth Low Energy beacons and a mobile app, this problem could be solved. BLE beacons broadcast packets of information which includes the RSSI, which could be used to determine how far the user is from a beacon. By placing a network of beacons in specific positions in an indoor environment, we would be able to detect where the user is located indoors. Using a mobile app, we could utilize the network of beacons to locate the user and guide them from their current location to their destination. For our project, we would be using SCSE as our environment. We first started by testing the feasibility of using beacons to detect the user in an indoor environment. Once we established that it was possible, we started working on the mobile app for indoor localization and indoor navigation. User testing was conducted to gather feedback of the mobile app and improvements was made. The goal of this project is to allow the users to be able to navigate between the various laboratories inside SCSE using a network of BLE beacons and a mobile app. The result from this would determine whether beacons, together with a mobile app, could be a viable solution for indoor localization and indoor navigation.